Pengaruh Employee Engagement Dan Knowledge Sharing Terhadap Kualitas Kinerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Mediasi - Faqqor, Muhammad Naazhir Dzul; Atho’illah, Akhmad Yunan (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
Research entitled the influence of employee engagement and knowledge sharing on the quality of employee performance with organizational culture as a mediating variable: case study at UD. Friends of Sidoarjo Farmers. This research uses a quantitative type of research. The type of data used in this research is primary data which comes from taking a questionnaire using a 1-5 Likert scale. Option one is a statement of strongly disagree and option five is a statement of strongly agree. Based on this research, the results show that employee engagement has an effect on organizational culture with a p value of 0.000, knowledge sharing has an effect on organizational culture with a p value of 0.0001, employee engagement has no effect on the quality of employee performance and has a p value of 0.247, knowledge sharing influences the quality of employee performance with a p value of 0.006, organizational culture mediates the relationship between employee engagement and the quality of employee performance with a p value of 0.009, and organizational culture mediates the relationship between knowledge sharing and the quality of employee performance with a p value of 0.021. Keywords: Employee engagement, knowledge sharing, organizational culture, and quality of employee performance.